118.4 Diurnal Cortisol Variation and Cortisol Response to an MRI Stressor in Schizophrenia and Bipolar Disorder - Green, Melissa (Schizophr Bull, 2017)
Background: Markers of HPA axis function are increasingly reported as disrupted in schizophrenia (SZ) and bipolar disorder (BD). These markers include aberrant diurnal cortisol rhythm, and/or cortisol responses to stress or pharmacological manipulation in SZ and BD, while associations between cortisol dysfunction and illness characteristics remain unclear. Methods: In this study, we examined cortisol levels of SZ and BD participants, relative to healthy controls (HC), using spline embedded linear mixed models, to determine group differences (a) at waking, (b) 45 minutes after waking (with the difference between a and b representing the Cortisol Awakening Response; CAR), (c) during the post-CAR decline, and (d) in reaction to a stressor (MRI scan). Results: In SZ, the cortisol response to the MRI stressor showed a significant absence of the expected increase in cortisol response to stress that was seen in both the BD and HC groups; notably, greater levels of anxiety were associated with this blunted cortisol response to stress in SZ patients. In addition, waking cortisol levels were greater in BD relative to SZ, but neither the SZ nor the BD groups deviated from HCs on measures of waking cortisol levels, CAR, or immediate post-CAR decline. In BD, longer illness duration was associated with a steeper incline in CAR and lower levels of waking cortisol; In SZ, higher antipsychotic medication dosage was associated with a steeper incline of the CAR, while greater positive symptom severity was associated with a more blunted CAR. Conclusion: The findings of reduced cortisol response to a stressor in SZ concord with previous reports of disjunction between felt emotions/stress and physiological responses during emotion regulation in SZ. Associations with clinical indices suggest that cortisol responses may normalize with medication (in SZ) and longer illness duration (in BD); the lack of group differences in waking cortisol levels or CAR, relative to HCs in this adult sample of patients with established illness aligns with altered HPA function during earlier periods of illness, as shown in recent studies of ultra-high risk and first-episode psychosis samples.